PROSEDUR PERENCANAAN UNTUK KAPAL-KAPAL IKAN BERUKURAN KECIL - Sugeng, Sunarso (Diponegoro University, 2009)
Design procedure of small fishing vesels, to develop a fishing boat was required the specification datas. Thespecification datas consist of compile planning stages, steps start from picture planning, fabrication,assembling, erection. Specificaton of picture planning process and ship have to be adapted for generalconditions of the ship type to be woke up. To get result of good planning to be required by detailed data fromship to be made by considering: how big wanted of the ship size measure,or which is the value of Vfh/â–¼ ( m3 /ton),where is the ship will be operated, what the the kind of fishing gear will be supported to the ship how longtime will be needed,is required in once operate for, and others. This matter is meant to get result of planningmatching with wanted ship type, is later;then conducted by calculation and result is poured in the form of shipplanning pictures